2012
DOI: 10.1631/jzus.b1100117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin-like growth factor-1 on the properties of mesenchymal stem cells in vitro

Abstract: Abstract:Objective: To explore the effects of insulin-like growth factor-1 (IGF-1) on migration, proliferation and differentiation of mesenchymal stem cells (MSCs). Methods: MSCs were obtained from Sprague-Dawley rats by a combination of gradient centrifugation and cell culture techniques and treated with IGF-1 at concentrations of 5-20 ng/ml. Proliferation of MSCs was determined as the mean doubling time. Expression of CXC chemokine receptor 4 (CXCR4) and migration property were determined by flow cytometry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 22 publications
3
32
0
2
Order By: Relevance
“…Regarding the proliferation curve proliferation increased after addition of IGF-1whichwas in accordance with HUANG et al who hypothesized that IGF-1 may play an important role in proliferation, migration, and differentiation of MSCs during transplantation. [40]Contrary to this Li et al observed that MSCs cultured in vitro with IGF-1 at final concentrations of 2.5, 5.0 and 10.0 ng/ml for 48 h did not affect the rate of proliferation. Therefore, whether this result was due to inadequate concentrations of IGF-1 or the culture time was too short needs to be further investigated [38].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Regarding the proliferation curve proliferation increased after addition of IGF-1whichwas in accordance with HUANG et al who hypothesized that IGF-1 may play an important role in proliferation, migration, and differentiation of MSCs during transplantation. [40]Contrary to this Li et al observed that MSCs cultured in vitro with IGF-1 at final concentrations of 2.5, 5.0 and 10.0 ng/ml for 48 h did not affect the rate of proliferation. Therefore, whether this result was due to inadequate concentrations of IGF-1 or the culture time was too short needs to be further investigated [38].…”
Section: Discussionmentioning
confidence: 95%
“…It had been reported that Cardiac troponin T is the earliest marker of myogenic differentiation [40]. It is essential for myofibrillar ATPase activity and is expressed in the heart of human and required for contractility of muscle [35].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin-like growth factor 1-IGF-1 IGF-1 has been shown to reduce the doubling time of mesenchymal stem cells (MSC), improve MSC proliferation, and enhance CXCR4 expression (Huang et al, 2012). IGF-1 also a demonstrated role in modulating cardiovascular function.…”
Section: Fibroblast Growth Factor -Fgfmentioning
confidence: 99%
“…В ýкспериментах на мышах показана роль SDF-1/CXCR4-рецептора в индукции (запуске) рекрутирования костномоз-говых клеток-предшественниц в левый желудочек после внутривенного их введения [16]. Совсем не-давно появилось исследование, касающиеся роли insulin-like growth factor 1 (IGF-1) в регуляции хоуминга MSCs [17,18].Метаболический фон в поврежденной ткани влияет на пролиферацию и дифференцировку мигрировавших клеток-предшественниц. Еже-дневные инъекции различных метаболитов мы-шам-реципиентам в течение 6 сут, предшеству-ющих летальному облучению и трансплантации сингенного костного мозга, приводят к образова-нию на селезенках большего количества колоний, чем у неподготовленных животных: при введении сукцината натрия на 78,6%, а β-оксибутирата на-трия, инозина или цАМФ на 67,9; 74,1 и 108% соответственно.…”
unclassified
“…В ýкспериментах на мышах показана роль SDF-1/CXCR4-рецептора в индукции (запуске) рекрутирования костномоз-говых клеток-предшественниц в левый желудочек после внутривенного их введения [16]. Совсем не-давно появилось исследование, касающиеся роли insulin-like growth factor 1 (IGF-1) в регуляции хоуминга MSCs [17,18].…”
unclassified